Degenerated graphite nodules influence on fatigue crack paths in a ferritic ductile cast iron - Francesco Iacoviello; Vittorio Di Cocco (Fracture and Structural Integrity)
Focusing on ferritic-pearlitic DCIs, these alloys are characterized by a microstructure that ranges from a fully ferritic to a completely pearlitic matrix, and they are widely used for many applications (e.g. wheels, gears, crankshafts in cars, exhaust manifolds, valves, flywheels, boxes bearings, hubs, shafts, valves, flanges, pipelines ...). Considering the graphite elements, their morphology can be considered as degenerated when its nodularity is too low and this can be due to different causes (e.g., a partially failed nodularization process or a wrong inoculant). In this work, a ferritic DCI with degenerated nodules was obtained by means of an annealing treatment and the fatigue crack propagation resistance was investigated by means of fatigue crack propagation tests performed according to ASTM E647, focusing on the influence of degenerated graphite nodules on the fatigue crack paths. This analysis was performed both analysing the crack path profile by means of a scanning electron microscope (SEM) and by means of a SEM fracture surfaces analysis.